Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/suco.202000131
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the chloride permeability of steel–concrete interface based on concretes of different stability

Abstract: The deterioration of reinforced concrete structures caused by chloride‐induced corrosion is a major threat to their service life. Previous studies show that defects in the steel–concrete interface have a significant impact on the corrosion process of steel bars. Study on the chloride permeability of steel–concrete interface is very important for revealing the mechanism. In this article, we devised a new experimental method named chloride penetration depth test which was used to evaluate the chloride permeabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Panesar and Shindman [11] also reported that the transport properties varied along the casting direction, and the durability performance was worse for the top surface of concrete specimens in comparison to the bottom surface. In authors' prior studies [12,13], it was found that due to the occurrence of CA settlement, when the height position of concrete core samples increased from 150 to 750 mm, the chloride permeability increased by 50%, resulting in earlier corrosion initiation of steel bars arranged at a higher position.…”
Section: Introductionmentioning
confidence: 99%
“…Panesar and Shindman [11] also reported that the transport properties varied along the casting direction, and the durability performance was worse for the top surface of concrete specimens in comparison to the bottom surface. In authors' prior studies [12,13], it was found that due to the occurrence of CA settlement, when the height position of concrete core samples increased from 150 to 750 mm, the chloride permeability increased by 50%, resulting in earlier corrosion initiation of steel bars arranged at a higher position.…”
Section: Introductionmentioning
confidence: 99%
“…The settlement of CAs has an adverse impact on the surface appearance, design strength and durability of hardened concrete. This may cause significant problems, such as the decline in mechanical strength, increased shrinkage and cracking, and the reduction of chemical erosion resistance, all of which are detrimental to the performance of reinforced concrete structures [14][15][16][17][18][19][20][21]. However, due to the opacity of concrete, the direct observation of CA settlement with naked eye is impossible.…”
Section: Introductionmentioning
confidence: 99%